2023
DOI: 10.3390/v15041025
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Tolerability and Prescribing Choice of Antiviral Molecules Molnupiravir, Remdesivir and Nirmatrelvir/r: A Real-World Comparison in the First Ten Months of Use

Abstract: In 2022, three antiviral drugs—molnupiravir, remdesivir and nirmatrelvir/ritonavir—were introduced for treatment of mild-to-moderate COVID-19 in high-risk patients. The aim of this study is the evaluation of their effectiveness and tolerability in a real-life setting. A single-center observational study was set up, with the involvement of 1118 patients, with complete follow-up data, treated between the 5th of January and the 3rd of October 2022 at Santa Maria Goretti’s hospital in Latina, Central Italy. A univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…The impact of vaccination on TLN was also highlighted by Li et al In their study, the authors showed that TLN was increased according to aging, female gender, fever, cough, and disease severity while consistently shortened according to vaccine doses [24]. Similar findings were reported by Del Borgo et al in a prospective study conducted in Italy, confirming the efficacy of vaccinations in reducing TLN [25].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The impact of vaccination on TLN was also highlighted by Li et al In their study, the authors showed that TLN was increased according to aging, female gender, fever, cough, and disease severity while consistently shortened according to vaccine doses [24]. Similar findings were reported by Del Borgo et al in a prospective study conducted in Italy, confirming the efficacy of vaccinations in reducing TLN [25].…”
Section: Discussionsupporting
confidence: 72%
“…A shorter median time was described for nirmatrelvir/ritonavir when compared to remdesivir and molnupiravir (8 vs. 10 days). In this study, 230 people received remdesivir three-day course, 499 molnupiravir, and 398 nirmatrelvir/ritonavir [25]. The efficacy of nirmatrelvir/ritonavir was reported in a prospective study where it was compared with sotrovimab.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevention of COVID-19, we have learned more about the efficacy of early antiviral therapies. The studies presented by Del Borgo et al and De Vito et al [ 2 , 3 ] evaluated the efficacy of antiviral therapies, confirming the results from the available literature [ 4 , 5 ]. Rombini et al, on the contrary, evaluated the efficacy of a Nucleoside Reverse Transcriptase Inhibitor (NRTI) already approved for the treatment of HIV.…”
supporting
confidence: 70%
“…On the other hand, DAA has maintained their activity across multiple variants due to the high conservation of the targeted viral enzymes [ 7 ]. However, current DAA may be unable to fully prevent severe disease progression, and their use is limited by a number of drug–drug interactions (NRM), inconvenient administration (RDV), or mutagenicity concerns (MNP) [ 8 ]. Indeed, the development of novel drugs or different therapeutic approaches remains a key priority [ 9 ].…”
Section: Introductionmentioning
confidence: 99%